2021
DOI: 10.1101/2021.01.07.425819
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using dual-calibrated functional MRI to map brain oxygen supply and consumption in multiple sclerosis

Abstract: Evidence suggests that cerebrovascular function and oxygen consumption are altered in multiple sclerosis (MS). Here, we quantified the vascular and oxygen metabolic MRI burden in patients with MS (PwMS) and assessed the relationship between these MRI measures of and metrics of damage and disability. In PwMS and in matched healthy volunteers, we applied a newly developed dual-calibrated fMRI method of acquisition and analysis to map grey matter (GM) cerebral blood flow (CBF), oxygen extraction fraction (OEF), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…Certainly, hypoperfusion in MS has been recognised for over 70 years [ 12 ], and as methods to measure perfusion have become more sophisticated, the overwhelming finding is of very significant hypoperfusion in both relapsing–remitting (RRMS) and primary and secondary progressive MS (PPMS and SPMS) [ 7 , 8 , 9 ] that significantly correlates with disability [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Some studies have considered whether the reduction in cerebral blood flow is likely to be just a secondary consequence of reduced demand and cerebral atrophy, or whether it is a primary cause of damage, and the clear conclusion is that the reduction is a primary event probably causing pathology and thereby disability [ 7 , 8 , 14 , 19 , 20 , 21 , 22 , 23 , 24 ]. Hypoperfusion is likely to result in tissue hypoxia, and there is substantial evidence that the MS brain is actually hypoxic, including the expression of hypoxia‐related antigens [ 25 , 26 ], the upregulation of genes induced by ischaemic preconditioning [ 25 , 26 , 27 , 28 ] and the presence of lesions characterised by hypoxia‐like demyelination [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, hypoperfusion in MS has been recognised for over 70 years [ 12 ], and as methods to measure perfusion have become more sophisticated, the overwhelming finding is of very significant hypoperfusion in both relapsing–remitting (RRMS) and primary and secondary progressive MS (PPMS and SPMS) [ 7 , 8 , 9 ] that significantly correlates with disability [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Some studies have considered whether the reduction in cerebral blood flow is likely to be just a secondary consequence of reduced demand and cerebral atrophy, or whether it is a primary cause of damage, and the clear conclusion is that the reduction is a primary event probably causing pathology and thereby disability [ 7 , 8 , 14 , 19 , 20 , 21 , 22 , 23 , 24 ]. Hypoperfusion is likely to result in tissue hypoxia, and there is substantial evidence that the MS brain is actually hypoxic, including the expression of hypoxia‐related antigens [ 25 , 26 ], the upregulation of genes induced by ischaemic preconditioning [ 25 , 26 , 27 , 28 ] and the presence of lesions characterised by hypoxia‐like demyelination [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…3,811 In any case, EOD may serve as a valuable clinical biomarker that is sensitive to underlying capillary, pericyte or mitochondrial dysfunction, e.g., in patients with neurovascular and degenerative diseases ranging from carotid artery stenosis and stroke to Alzheimer’s disease. 8,12 Importantly, recent studies in patients with, e.g., unilateral stenosis and occlusion 13 or multiple sclerosis 14 indicated that EOD could provide complementary information – regarding hemodynamic compromise and the association of such impairments with other variables such as age or white matter lesion volume – that is distinct from CBF, OEF or CMRO 2 .…”
Section: Introductionmentioning
confidence: 99%